Generalized Contractive Mappings and Weakly α-Admissible Pairs in G-Metric Spaces. (16th August 2014) - Hussain, N.; Parvaneh, V.; Hoseini Ghoncheh, S. J.
Abstract : The aim of this paper is to present some coincidence and common fixed point results for generalized (ψ, φ )-contractive mappings using partially weakly G -α -admissibility in the setup of G -metric space. As an application of our results, periodic points of weakly contractive mappings are obtained. We also derive certain new coincidence point and common fixed point theorems in partially ordered G -metric spaces. Moreover, some examples are provided here to illustrate the usability of the obtained results.